2021
DOI: 10.1111/ijd.15669
|View full text |Cite
|
Sign up to set email alerts
|

Association between long noncoding RNA taurine‐upregulated gene 1 and microRNA‐377 in vitiligo

Abstract: Background Taurine-upregulated gene 1 (TUG1) is one of the long noncoding RNAs (lncRNAs) that plays a role in melanogenesis. is a conserved noncoding RNA that regulates angiogenesis and promotes oxidative stress. Peroxisome proliferator-activated receptors (PPARs) are components of the nuclear hormone receptor superfamily. PPAR-c activators stimulate melanogenesis. Interleukin (IL)-17 has been implicated in the pathogenesis of several immunological diseases. This work aimed at detecting the expression levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
1
9
0
Order By: Relevance
“…However, PPAR-γ and lncRNA TUG1 were significantly downregulated in vitiligo patients. To conclude, dysregulated miRNA-377 might contribute to the pathogenesis of vitiligo through PPAR-γ downregulation and IL-17 upregulation (Alhelf et al, 2021).…”
Section: Mirna-377mentioning
confidence: 89%
See 1 more Smart Citation
“…However, PPAR-γ and lncRNA TUG1 were significantly downregulated in vitiligo patients. To conclude, dysregulated miRNA-377 might contribute to the pathogenesis of vitiligo through PPAR-γ downregulation and IL-17 upregulation (Alhelf et al, 2021).…”
Section: Mirna-377mentioning
confidence: 89%
“…MiR-155 upregulation might regulate the inflammatory stimuli-induced MITF-M downregulation. Elevated miRNA-377 expression might contribute to the pathogenesis of vitiligo through PPAR-γ downregulation and IL-17 upregulation (Alhelf et al, 2022). MiR-3940-5p expression was decreased in PBMCs isolated from NSV patients (Wang et al, 2015).…”
Section: Immune Imbalancementioning
confidence: 99%
“…25 Studies on the role of miRNAs in vitiligo have been reported. [26][27][28][29][30][31][32] As an miRNA sponge, circRNAs can regulate gene transcription, modulate the expression of parental genes, and participate in the occurrence and development of various diseases. 33 Some circRNAs regulate inflammation, cell proliferation, and immunity of various cells involved in the pathogenesis of vitiligo, and ceRNA regulation mechanism may be involved in the oxidative stress-mediated melanocyte injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, further processing is needed to obtain mature miRNA to work. For example, although the precursor of miR‐675 is H19, the bases of miR‐675 are mainly C and G, while the bases of H19 are mainly G, which may be the structural basis for different functions (Alhelf M, et al, 2021). Since lncRNA also has 3'UTR, miRNA can bind to 3'UTR of lncRNA just as it acts with mRNA, thus directly inhibiting lncRNA.…”
Section: Interaction Among Lncrna Mirna and Mrnamentioning
confidence: 99%